Functional characterization and stability improvement of a ‘thermophilic-like’ ene-reductase from Rhodococcus opacus 1CP - Riedel, Anika; Mehnert, Marika; Paul, Caroline E.; Westphal, Adrie H.; van Berkel, Willem J. H.; Tischler, Dirk (Frontiers in Microbiology, 2015)
Ene-reductases are widely applied for the asymmetric synthesis of relevant industrial chemicals. A novel ene-reductase OYERo2 was found within a set of 14 putative Old Yellow Enzymes (OYEs) obtained by genome mining of the actinobacterium Rhodococcus opacus 1CP. Multiple sequence alignment suggested that the enzyme belongs to the group of ‘thermophilic-like’ OYEs. OYERo2 was produced in Escherichia coli and biochemically characterized. The enzyme is strongly NADPH dependent and uses non-covalently bound FMNH2 for the reduction of activated α,β-unsaturated alkenes. In the active form OYERo2 is a dimer. Optimal catalysis occurs at pH 7.3 and 37 °C. OYERo2 showed highest specific activities (4550 U mg-1) on maleimides, which are efficiently converted to the corresponding succinimides. The OYERo2-mediated reduction of prochiral alkenes afforded the (R)-products with excellent optical purity (ee > 99%). OYERo2 is not as thermo-resistant as related OYEs. Introduction of a characteristic intermolecular salt bridge by site-specific mutagenesis raised the half-life of enzyme inactivation at 32 °C from 28 min to 87 min and improved the tolerance towards organic co-solvents. The suitability of OYERo2 for application in industrial biocatalysis is discussed.